Imagination, spontaneity and otherness - Sabolius, Kristupas (Religija ir kultūra, 2009)
The concept of identity in Western thinking consists in nothing other than establishing static and solid structure of Cartesian subject, whose existence is limited to the mere fact of thinking in which I, as a thinker, (cogitans) am never doing anything but constituting myself as an object (cogitatum). Phenomenology, back to Husserl and Sartre, provided us with a need of the dynamism of the consciousness, an almost „hydrographic concept“ of the flow of ego which could be grasped only as a compositional stream containing rhythm and orientation. On the other hand, Freud’s and, in particular, Lacan’s psychoanalysis discovered the heterogeneous reality of the Other, i.e. the Unconscious, which should be liberated from the false identity of the specular and imaginary ego. This paper, through the analysis of autonomous and resistant nature of imagination as spontaneity, i.e. combining and simultaneously criticizing phenomenological and psychoanalytic approaches, seeks to delegate the new task for imagination – that of invoking the Otherness in the constitution of myself.